Monsters in the dark: systematics and biogeography of the stygobitic genus Godzillius (Crustacea: Remipedia) from the Lucayan Archipelago - Ballou, Lauren; Iliffe, Thomas M.; Kakuk, Brian; Gonzalez, Brett C.; Osborn, Karen J.; Worsaae, Katrine; Meland, Kenneth; Broad, Kenneth; Bracken-Grissom, Heather; Olesen, Jørgen (European Journal of Taxonomy, 2021)
Remipedia is a stygobitic group commonly associated with coastal anchialine caves. This class consists of 12 genera, ten of which are found within the Lucayan Archipelago. Herein, we describe a new species within the genus Godzillius from Conch Sound Blue Hole, North Andros Island, Bahamas. Godzillius louriei sp. nov. is the third known remipede observed from a subseafloor marine cave, and the first from the Godzilliidae. Remipedes dwell within notoriously difficult to access cave habitats and thus integrative and comprehensive systematic studies at family or genus level are often absent in the literature. In this study, all species of Godzillius are compared using morphological and molecular approaches. Specifically, the feeding appendages of G. louriei sp. nov., G. fuchsi Gonzalez, Singpiel & Schlagner, 2013 and G. robustus Schram, Yager & Emerson, 1986 were examined using scanning electron microscopy (SEM). Species of Godzillius are identified based on the spines of maxilla 1 segment 4 and by the denticles on the lacinia mobilis of the left mandible. A molecular phylogeny using the mitochondrial 16S rRNA and nuclear histone 3 genes recovered G. louriei sp. nov. within the Godzillius clade and 16S genetic distances revealed a 13–15% difference between species of Godzillius.